Gaya Bahasa Asonansi dan Aliterasi pada Q.S At-Takwir Juz 30: Kajian Fonologi Fungsional Estetik - Latifah, Umi; Badrih, Moh. (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The focus of this research to analyzing patterns of the purpose of this study is to identify and analyze the patterns of assonance and alliteration in Q.S. At-Takwir, to understand how these phonological elements contribute to the aesthetic beauty and strengthen the meaning of the theological message contained in the surah. The research method used is a qualitative approach with a descriptive-analytical method. The data in this study are in the form of the text of Q.S. At-Takwir from the Qur'an. The stages of data analysis include data collection, identification and categorization, phonological analysis, data interpretation, drawing conclusions, and data validation. The results show that assonance creates a deep emotional atmosphere and strengthens the message, while alliteration adds rhythm, deepening the dramatic effect. Assonance and alliteration in Q.S. At-Takwir play an important role in beautifying the text, building rhythm, and strengthening the theology of the message, indicating that these phonological elements function more than just aesthetics, but as a means of conveying a deep spiritual message.